Engineered human angiogenin mutations in the placental ribonuclease inhibitor complex for anticancer therapy: Insights from enhanced sampling simulations. (19th May 2016) - Cong, Xiaojing; Cremer, Christian; Nachreiner, Thomas; Barth, Stefan; Carloni, Paolo
Abstract: Targeted human cytolytic fusion proteins (hCFPs) represent a new generation of immunotoxins (ITs) for the specific targeting and elimination of malignant cell populations. Unlike conventional ITs, hCFPs comprise a human/humanized target cell‐specific binding moiety (e.g., an antibody or a fragment thereof) fused to a human proapoptotic protein as the cytotoxic domain (effector domain). Therefore, hCFPs are humanized ITs expected to have low immunogenicity. This reduces side effects and allows long‐term application. The human ribonuclease angiogenin (Ang) has been shown to be a promising effector domain candidate. However, the application of Ang‐based hCFPs is largely hampered by the intracellular placental ribonuclease inhibitor (RNH1). It rapidly binds and inactivates Ang. Mutations altering Ang's affinity for RNH1 modulate the cytotoxicity of Ang‐based hCFPs. Here we perform in total 2.7 µs replica‐exchange molecular dynamics simulations to investigate some of these mutations—G85R/G86R (GGRRmut ), Q117G (QGmut ), and G85R/G86R/Q117G (GGRR/QGmut ). GGRRmut turns out to perturb greatly the overall Ang‐RNH1 interactions, whereas QGmut optimizes them. Combining QGmut with GGRRmut compensates the effects of the latter. Our results explain the in vitro finding that, while Ang GGRRmut ‐based hCFPs resist RNH1 inhibition remarkably, Ang WT‐ and Ang QGmut ‐based ones are similarly sensitive to RNH1 inhibition, whereas Ang GGRR/QGmut ‐based ones are only slightly resistant. This work may help design novel Ang mutants with reduced affinity for RNH1 and improved cytotoxicity.